An experimental investigation of the effects of out-of-plane loading on the in-plane seismic response of SC wall piers. (1st July 2019) - Terranova, Brian; Bhardwaj, Saahastaranshu; Whittaker, Andrew; Varma, Amit; Orbovic, Nebojsa
Highlights: Experimental study investigating effects of OOP loading on IP response of SC walls. Study focuses on the magnitude of the OOP load and tie bar spacing. OOP loading is significant when it exceeds inclined cracking capacity of concrete. Tie bar spacing of less than or equal to one-half the wall thickness is recommended. Data provides starting point for validation of numerical models. Abstract: A significant number of numerical and experimental studies have addressed the in-plane (IP) seismic response of SC walls and wall piers, but the effect of out-of-plane (OOP) loading on IP response has not been investigated. Out-of-plane shears and moments will develop at load and/or stiffness discontinuities, with OOP shearing forces possibly cracking infill concrete and OOP moments possibly imposing significant axial stresses in the steel faceplates. Three rectangular SC wall piers with an aspect ratio of 0.6 were built and tested to investigate the effects of OOP loading on IP cyclic response. The variables considered in the experiments were magnitude of OOP loading and tie bar spacing. The magnitude of the OOP loading ranged between the nominal shear capacity of plain concrete and that sufficient to produce inclined cracking in the wall. The effect of OOP loading on IP response becomes very significant as the applied OOP loading equals or exceeds the inclined cracking capacity of the concrete. For SC wall piers subjected to OOP shear stresses greater than that associated with inclined cracking, a tie bar spacing of less than or equal to one-half the wall thickness is recommended. Additional experiments are needed to characterize the effect of shear span of the OOP loading on IP response. Numerical simulations and additional design guidance are presented elsewhere.